Diversity in local rice germplasm and rice farming: A case study of thailand - Benjavan Rerkasem (2018)
Local rice varieties or land races continue to play a key role in rice farming in many parts of Asia, especially in and near the center of diversity of Oryza sativa. This paper provides a review of work done in Thailand, showing how local varieties meet the need of rice farming in areas not reached by improved varieties for ecological, economic and social reasons, while serving to maintain genetic diversity in the field. Far from being archaic inferior types, local rice varieties can outyield modern varieties in these difficult places. Continuing seed selection by farmers resulted in individual seed lots with uniform appearance of the grain and plants, including in those characteristics that are important in crop management such as flowering and maturity time. Such uniformity that satisfies rice growers, traders and consumers, however, hides enormous genetic diversity measurable with molecular markers as well as in useful traits. Variation is found between seed of the same varieties kept by different farmers and within individual seed lots, as well as between different varieties. Hybridization among local rice varieties and also with the common wild rice (O. rufipogon) is likely to be enhanced by traits for cross pollination, e.g. extruded stigma and pollen shedding outside the glumes. Genetic diversity of this important germplasm is maintained by farmers' seed management and selection. Regular seed turnover and exchanges add to the sorting process and genetic differentiation. © 2008 Taylor & Francis Group, LLC.